2019
DOI: 10.1007/s40266-019-00652-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Levobupivacaine Following Fascia Iliaca Compartment Block in Elderly Patients

Abstract: Background: Fascia iliaca compartment block (FICB) is an increasingly popular analgesic technique in elderly patients with hip fracture. Despite requiring large volumes of local anaesthetic, there is no safety data on plasma concentration of local anaesthetic after FICB in elderly patients. Objectives: The aim was to determine the safety and pharmacokinetic profile of a 75 mg levobupivacaine (30ml 0.25%) FICB dose in patients aged ≥80 years with a fractured neck of femur. Methods: This was a single-arm descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…As demonstrated by the product ion spectra for bupivacaine and the deuterated internal control D9-bupivacaine (Figure 1), although lo- cal anesthetics can be very close in size and chemistry, they can be distinguished from one another by chromatography [6]. The data in this study are in general agreement with the gas chromatography-mass spectrometry data described by Odor et al [7]. Although LC-MS/MS is an accurate analytical method, it cannot be used for real-time detection of toxic plasma levels of levobupivacaine, as blood sample preparation and running of the LC-MS/MS method takes over 8 hours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As demonstrated by the product ion spectra for bupivacaine and the deuterated internal control D9-bupivacaine (Figure 1), although lo- cal anesthetics can be very close in size and chemistry, they can be distinguished from one another by chromatography [6]. The data in this study are in general agreement with the gas chromatography-mass spectrometry data described by Odor et al [7]. Although LC-MS/MS is an accurate analytical method, it cannot be used for real-time detection of toxic plasma levels of levobupivacaine, as blood sample preparation and running of the LC-MS/MS method takes over 8 hours.…”
Section: Discussionsupporting
confidence: 91%
“…The data from this study have added to the pharmacokinetic profile of plasma levobupivacaine of older patients following FICB for hip fracture surgery. This local anesthetic technique was demonstrated to be safe for use in older patients supporting previous results [7]. The data collected can be used to help local anesthetic dosing in older patients and improve local anesthetic safety.…”
Section: Discussionsupporting
confidence: 78%
“…Visual analogue scores (VAS) were calculated during positioning for spinal anesthesia, and it was concluded that VAS scores were lower in patients who received FICB. In a similar study, Odor et al studied the pharmacokinetic profile of levobupivacaine for fascia iliaca block in patients above 80 years [9]. They used 30 ml of 0.25% levobupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…They found C max similar in both groups with means of approximately 1 mg × L −1 and faster absorption from the transversus abdominis plane. One study investigated the pharmacokinetics of levobupivacaine after a single bolus of the drug to the fascia iliaca compartment in elderly frail patients with a fractured neck of the femur [21]. The authors reported the highest C max as 1.42 mg × L −1 and that none of their patients exhibited any symptoms of local anesthetic systemic toxicity (LAST).…”
Section: Discussionmentioning
confidence: 99%